2012
DOI: 10.1177/0885066612453542
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Use of Prophylaxis for Stress-Related Mucosal Disease in Patients Admitted to the Intensive Care Unit

Abstract: Stress ulcer prophylaxis administration in this ICU is inconsistent and includes both underutilization and overutilization. Educating physicians and implementing hospital protocols could improve use patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 35 publications
0
24
0
1
Order By: Relevance
“…Difficulties in identifying high‐risk patients may lead to this under‐ or overuse of SUP. In a US survey from 2012, 53% either received SUP without a clinical indication or did not receive SUP when indicated . Even though the evidence supporting the American Society of Health‐System Pharmacists criteria is modest, inappropriate use of SUP is common and overuse of SUP may be a more significant problem than underuse.…”
Section: Discussionmentioning
confidence: 99%
“…Difficulties in identifying high‐risk patients may lead to this under‐ or overuse of SUP. In a US survey from 2012, 53% either received SUP without a clinical indication or did not receive SUP when indicated . Even though the evidence supporting the American Society of Health‐System Pharmacists criteria is modest, inappropriate use of SUP is common and overuse of SUP may be a more significant problem than underuse.…”
Section: Discussionmentioning
confidence: 99%
“…Gastrointestinal (GI) stress ulcer are common in critically ill patients who require admission to Intensive Care Unit (ICU), whereas 75–100% of ICU patients experience mucosal injury as early as the first 24 h of ICU admission. [ 1 2 ] Moreover, occult bleeding occurs in 15–50% of critically ill patients and 5–25% of these patients experience overt bleeding if they do not receive stress ulcer prophylaxis (SUP). [ 3 ]…”
Section: Introductionmentioning
confidence: 99%
“…High morbidity and mortality of stress ulcer-related bleeding and concerns about cost and adverse effects of SUP administrations such as pneumonia and Clostridium difficile infections, provoked different studies to determine the pattern of SUP prescription in ICU and non-ICU patients. [ 2 3 4 5 6 7 8 9 10 11 12 13 ]…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of histamine‐2‐receptor antagonists (H2RAs) made intravenous administration possible, and a randomized clinical trial (RCT) in adult ICU patients reported a lower incidence of GI bleeding in patients receiving H2RA compared with sucralfate . Proton pump inhibitors (PPIs) were introduced later on, and today the majority of prescribed SUP for patients in all ages is H2RAs or PPIs …”
Section: Introductionmentioning
confidence: 99%